2019
DOI: 10.1111/plb.12977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought and N level on the interactions of the root hemiparasite Rhinanthus alectorolophus with a combination of three host species

Abstract: Increasing nitrogen deposition and more frequent drought events are likely to change plant interactions in natural grasslands. Both factors may also influence the interactions between hemiparasitic plants, regarded as keystone species in many grasslands, and their host species.• We grew a combination of three suitable hosts, a grass, a forb and a legume, with and without the hemiparasite Rhinanthus alectorolophus at three levels of nitrogen (N) and two levels of water availability in a factorial design.• Bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…Irrespective of water and nitrogen treatments, infection with the native parasitic vine strongly decreased total biomass of the invasive shrub by 70%. Similarly, Korell et al (2019) found that R. alectorolophus negatively affected growth of three perennial hosts, regardless of water 9 nitrogen treatments. We also observed that infection had a greater impact on shoot biomass and shoot : root ratio of hosts in high water than low water, irrespective of N supply.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Irrespective of water and nitrogen treatments, infection with the native parasitic vine strongly decreased total biomass of the invasive shrub by 70%. Similarly, Korell et al (2019) found that R. alectorolophus negatively affected growth of three perennial hosts, regardless of water 9 nitrogen treatments. We also observed that infection had a greater impact on shoot biomass and shoot : root ratio of hosts in high water than low water, irrespective of N supply.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, Korell et al . (2019) found that R. alectorolophus negatively affected growth of three perennial hosts, regardless of water × nitrogen treatments. We also observed that infection had a greater impact on shoot biomass and shoot : root ratio of hosts in high water than low water, irrespective of N supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first hypothesis predicts better establishment of HP and larger suppressive effect of HP on a host in nutrient-rich soils as HP may benefit from a direct nutrient supply and better host quality (Irving & Cameron, 2009;Korell et al, 2020), while the second hypothesis suggests better performance of HP in nutrient-limiting soils due to decreased competition for light (Hejcman et al, 2011;Korell et al, 2020;Těšitel et al, 2015). There also is some evidence that HP may perform equally well regardless of soil fertility (Korell et al, 2020). In addition, we focused on density-dependent effects of the RA effect on tall fescue height and biomass ( Figure 1) and discuss some implications and recommendations for applied grassland management.…”
Section: Core Ideasmentioning
confidence: 99%
“…Combinations of multiple air pollutants are the focus of Papazian & Blande (), who review plant physiological responses and ecological perspectives in natural and managed ecosystems, including potential uses of plants to mitigate air pollution, whereas Korell et al () investigated the effects of drought and nitrogen deposition on the interactions of a root hemiparasite ( Rhinanthus alectorolophus ) with three host species. De Micco et al () analysed whether dust deposition can change leaf anatomical functional traits and the efficiency of the photosynthetic apparatus in Centranthus ruber .…”
mentioning
confidence: 99%